2015
DOI: 10.4314/star.v4i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Radical Scavenging Efficacy of Leaf and Flower of <i>Aristolochia indica</i> Linn.

Abstract: The present study was performed to screen antibacterial, antifungal and radical scavenging efficacy of leaf and flower extract of Antibacterial and antifungal activity was evaluated by agar well diffusion and poisoned food technique respectively. Radical scavenging potential was determined by DPPH free radical scavenging assay. Overall, Leaf extract and flower extract displayed stronger antibacterial and antifungal activity respectively. Leaf extract was found to scavenge DPPH radicals more effectively when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…While for the methanolic fraction, S. aureus was the only inhibited bacteria (17.2 and 27 mm). Our study shared the same results with the study of Naik et al 16 who investigated the antibacterial activity of A. indica leaf extract and flowers against gram (+) and gram (−) bacteria also using the diffusion method on wells. This activity could be explained by the disruption of the permeability barrier of the bacterial membrane.…”
supporting
confidence: 89%
“…While for the methanolic fraction, S. aureus was the only inhibited bacteria (17.2 and 27 mm). Our study shared the same results with the study of Naik et al 16 who investigated the antibacterial activity of A. indica leaf extract and flowers against gram (+) and gram (−) bacteria also using the diffusion method on wells. This activity could be explained by the disruption of the permeability barrier of the bacterial membrane.…”
supporting
confidence: 89%
“…At 1000 μg/ml concentration, aqueous stem extract of A. indica showed higher scavenging activity of 66.66±4.67% compared to chloroform leaf extract of 48.33±3.38% in DPPH method (Subramaniyan et al, 2015). Naik et al (2015) found the ethyl alcohol extracts of leaves and flowers of A. indica at 100µg/ml concentration showed 48.68% and 10.52% DPPH radical scavenging activity respectively where ascorbic acid was used as standard. The aerial parts of A. indica exhibited IC50 value of 7.325 µg/ml at 25 µg/ml concentration when tested by DPPH radical scavenging method using ascorbic acid as standard and IC50 value of 8.498 µg/ml at 10 µg/ml concentration when tested by superoxide anion radical scavenging method with curcumin as standard (Karan et al, 2012).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Venkatadri et al (2015) studied the whole plant extracts by agar well diffusion method against multidrug-resistant β-lactamases producing bacteria and ethanolic extract showed minimum inhibitory concentration values of 50-100 μg/ml and 100-200 μg/ml. Naik et al (2015) studied against three Gram-positive (Staphylococcus aureus, Bacillus coagulans, B. subtilis) and three Gram-negative (Escherichia coli, Pseudomonas aeruginosa and Salmonella typhi) bacteria. The leaf extract caused high inhibition of B. coagulans followed by B. subtilis and the least inhibition caused by leaf extract was recorded against S. aureus.…”
Section: Antimicrobial Activitymentioning
confidence: 99%